The Indonesian Guardianship and Indonesian Private International Law - Allagan, Tiurma Mangihut Pitta; Himmah, Dinda R; Hisana, Amirah (Indonesia Law Review, 2025)
The increasing of number of cross-border legal relationships, especially family legal relationships, is inevitable. For instance, it is also commonly accepted for a foreign national to have a legal-bond with children from another country, which is also known as intercountry adoption, guardianship and fostership. This paper aims to analyze and classify guardianship involving international dimension within the jurisdiction of Indonesia. The examination of this legal question would be on the basis of Indonesian Private International Law (PIL). The choice of law and the choice of jurisdiction are the basic analysis, further, as to whether the guardianships are in line with the prevailing regulations and mirroring the principle of the best interest of the child. The importance of this research question is in line with the consideration that the varied classification of custody leads to different legal consequences as well; both to the children and the parents, either the biological parents or the non-biological parents of the children.